PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN TENTANG HIPERTENSI KEHAMILAN TERHADAP UPAYA PEMELIHARAAN TEKANAN DARAH PADA IBU HAMIL DI DESA NGEBONG KECAMATAN DELANGGU KABUPATEN KLATEN - Rahayu Setyaningsih; Endang Dwi Ningsih; Megawati Ahmad (KOSALA : Jurnal Ilmu Kesehatan, 2014)
Abstract The Background of Pregnancy hipertension is the blood pressure increasing after 20 weeks of the gestation period â‰¥ 140 mmHg for systolic and â‰¥ 90 mmHg for diastolic. Pregnancy hipertension can be occured whenever the pregnant women do not keep maintaining their blood pressure at the normal level. The background of this case is caused by the poor health knowledge of the women regarding the pregnancy hipertension. The research aim to know the influence of the health education on the pregnant women to keep maintaining the blood pressure. The subject were the 30 pregnant women in Ngebong village, Delanggu Distric, Klaten city. The sampling technique is the saturated sampling (all the sample subject used). The questionnaire methode before and after the education is given. The data analized by â€œtâ€ test. The result based on the dependent paired â€œtâ€ test (uji t) with Î± = 5% (0,05); P value got 0,000 it indicate : P = 0,000 < Î± = 0,05 ; it means the hypothesis acceptable. The conclusion is having an influence of the health education of the blood hipertension on pregnancy given to make the effort on the pregnan women to keep maintaining their blood pressure in Ngebong village, Delanggu Distric, Klaten city. Keywords : Health education, Pregnancy hipertension, Keep Maintaining blood pressure